Trends of Colorectal Cancer Prevalence in Kazakhstan Related to Screening - Alma Zhylkaidarova; Dilyara Kaidarova; Kanat Batyrbekov; Oxana Shatkovskaya; Dinara Begimbetova (Korean Society of Gastrointestinal Endoscopy, 2021)
We carried out an analysis of the total incidence of colon cancer throughout Kazakhstan. Retrospectively, according to the regional reports on endoscopic screening, the study showed an increase in the age-related incidence of colorectal cancer (CRC) cases from 2004-2008 to 2009-2014. The peak of morbidity in both periods was noted in the age category of >70 years. The indicators of the territorial distribution of CRC incidence make it possible to divide the regions into areas with low or high rates of CRC. Specific indicators showed newly diagnosed cases of CRC stages I, II, III, and IV in 2004-2018. The incidence rates of stages I and II showed a two-fold increase (35%-67.4%) and the incidence of stage IV showed a decline from 19.3% to 13.1% and of stage III from 45.7% to 19.5% from 2004 to 2018, respectively. An analysis of CRC incidence throughout Kazakhstan showed an increase in the overall incidence. Since population-based CRC screening was introduced in 2011, the morbidity was found to increase for stages I and II.